ABELIAN VECTOR FIELD IN TELEPARALLEL GRAVITY WITH METRIC BIANCHI TYPE I - ALHAFISH (NIM : 10206097); Pembimbing : Prof. Dr. Triyanta, Ph. D, MUHAMAD
Teleparallel gravity is a gauge theory of translation group. In this theory torsion acts as a representation of the gravitational field by using the assumption that the curvature is zero and the tetrad field replacing metric as a factor of gravitational fieldÃ‚Â’s existence,. Teleparallel gravity is considered as a theory that can be used to describe the gravitational interaction of matter fields. In this final project, the gravitational interaction prescription defined in teleparallel gravity is applied to electromagnetic vector fields with the Bianchi type I metric as its background. The resulting vector field equations are then solved by using the exponential scale factor with the assumption that the Bianchi type I metric reduces to flat FLRW metric in the isotropic case. The solutions are extracted by using approximation method. We obtain that the frequency of the electromagnetic field is not constant but instead it depends on time (function of time). When the constant b approaches zero, the vector field solution reduces to the well-known plane wave solution.